Identification and Quantification of Anthocyanins in Various Organs of Potato Varieties (Solanum tuberosum L.) as Potential Visual Selection Markers During Breeding - Irina V. Kim; Muhammad A. Nawaz; Dmitry I. Volkov; Aleksey G. Klykov; Mayya P. Razgonova; Kirill S. Golokhvast (Plants)
Phenolic compounds, which are a large group of plant pigments, are recognized as important antioxidants. The potato (Solanum tuberosum L.), particularly the pigmented varieties, could be a source of natural anthocyanins for producing dietary foods. In this study, we analyzed forty potato specimens from our germplasm collection and breeding nurseries using high-performance liquid chromatography (HPLC) and second-order mass spectrometry to identify anthocyanins. We found seven main anthocyanins in potato tubers: delphinidin-3-glucoside, delphinidin-3-rhamnosyl-5-glucoside, petunidin-3-glucoside, malvidin-3-glucoside, cyanidin-3-glucoside, cyanidin-3-rhamnosyl-5-glucoside, and pelargonidin-3-glucoside. Two anthocyanins were found in potato inflorescences: peonidin-3-coumaroyl glucoside and cyanidin-3-coumaroyl glucoside. On average, varieties from the group with red-purple inflorescences contained 187.6 mg/kg of anthocyanins. Genotypes with white corollas had an anthocyanin content below 0.5 mg/kg or between 1.3 and 3.6 mg/kg. Two potato varieties, Vasilek (605.2 mg/kg) and Fioletovyi (501.1 mg/kg), with blue-purple corollas, had the highest total anthocyanin content. Studying the anthocyanin profile of leaves allowed us to identify eleven anthocyanins. The highest anthocyanin content (331.3 mg/kg) was found in varieties with purple or blue-purple tubers, while the lowest content (an average of 15.1 mg/kg) was found in varieties with yellow or cream tubers. Genotypes with purple and blue-purple tuber skin had an average anthocyanin content of 190.7 mg/kg. The group with yellow and cream tubers had an insignificant anthocyanin content (1.2 mg/kg). Varieties from the group with pink tubers had an average anthocyanin content of 43.2 mg/kg. Thus, this study identified diagnostic traits that could be used to assess the morphological characteristics of potato genotypes.